Cervix Duplex in Simmental Cow - Gračner, Damjan (Array, 2005)
At the Clinic for the Internal diseases, a cow, Simmental breed, 2, 5 years old wass admitted. During the first artificial insemination of heifer the veterinarian in the field found out irregularities in the region of cervix uteri (cerix duplex) and at the owners request, the heifer was artificially inseminatede. He used two doses of semen for both cervical canales because it was not certain that they were passable. This anomaly did not cause any trouble during birth. The gynaecological examination at the Clinic confirmed a heredital anomaly of reproductive tract called cervix duplex. Both cervical canales were passable.